DISPLACEMENT WASHING OF SULPHITE AND KRAFT PULPS - Potůček, František; Rahman, Md. Mostafizur (Technická univerzita vo Zvolene, 2018)
Displacement washing of spruce sulphite and kraft pulps was simulated using a laboratory washing cell. Geometrical properties of pulp fibres, as well as intrinsic properties of spent red and black liquors were determined. The sulphite spruce pulp beds showed the intrinsic permeability of 3.0 x 10(-12) to 6.7 x 10(-12) m(2) and the specific resistance of 1.2 x 10(9) to 2.3 x 10(9) m kg(-1), while, for the kraft spruce pulp, the former was within the limits of 1.2 x 10(-12) to 3.0 x 10(-12) m(2) and the latter within the limits of 2.6 x 10(9) to 6.3 x 10(9) m kg(-1). The displacement washing process was described by the washing curves measured for lignosulphonates and/or alkali lignin. The wash yield determined for sulphite spruce pulp was found to be greater than that for kraft spruce pulp. The relationships between the wash yield, on one hand, and the Peclet number for each pulp sort and/or two independent dimensionless criteria for all data gathered for both pulp sorts on the other hand, were expressed by the correlation equations.
Vytěsňovací praní sulfitové a sulfátové buničiny
Keywords: displacement washing; sulphite pulp; kraft pulp; wash yield; Peclet number; vytěsňovací praní; sulfitová buničina; sulfátová buničina; výtěžek praní; Pécletovo kritérium